Theravada traditions : Buddhist ritual cultures in contemporary Southeast Asia and Sri Lanka - Holt, John, 1948- (University of Hawaii Press : University of Hawaii Press, 2017)
This is a study of very popular ritual celebrations observed by Buddhist monks and laity in each of the predominantly Theravada Buddhist cultures in Sri Lanka and Southeast Asia (Thailand, Myanmar, Laos and Cambodia.) The theoretical approach deployed guides the reader through the distinctiveness of each culture.